Unusual association of priapism with Wolfram syndrome - Chirantap Oza; Madhura Karguppikar; Vaman Khadilkar; Anuradha Khadilkar (Indian Journal of Child Health, 2021)
Wolfram syndrome is an autosomal recessive disorder resulting from mutation of WFS1 gene located on 4p16.1 and is characterized by diabetes insipidus (DI), diabetes mellitus (DM), optic atrophy, and sensorineural deafness with features of neurodegeneration, renal anomalies, and primary gonadal atrophy. Priapism itself is a rare disease with isolated reports in association with type-2 DM due to change in coagulation status causing endothelial dysfunction and local vascular thrombosis leading to ischemic priapism. Here, we present a case of a 14-year-old male with type-1 DM and optic atrophy who was presented to us with two episodes of priapism. He was suspected to have Wolfram syndrome and his genetic evaluation for WFS-1 gene confirmed the diagnosis. Our case suggests that priapism is an atypical association in patient with the Wolfram Syndrome due to hypercoagulability in type-1 DM which is rarely reported.